Evidence for a common mutation in hereditary pancreatitis. Issue 2 (April 1998) - Bell, S M; Bennett, C; Markham, A F; Lench, N J
Abstract : Hereditary pancreatitis is an autosomal dominant disorder with incomplete penetrance. It is characterised by recurring episodes of severe abdominal pain and often presents in childhood. Recently, a mutation in the cationic trypsinogen gene was identified in this disease. Previously, only one mutation at residue 117 of the trypsinogen gene has been found in the five separate hereditary pancreatitis families, four from the USA and one from Italy. Alteration of the Arg117 site is believed to disrupt a fail-safe mechanism for the inactivation of trypsin, leading to autodigestion of the pancreas under certain conditions. Molecular analysis of the trypsinogen gene was carried out on a hereditary pancreatitis family from the UK. The same G to A mutation at residue 117 was identified in this family, suggesting that this is a common mutation in hereditary pancreatitis.